Organisational caring ethical climate and its relationship with workplace bullying and post traumatic stress disorder: The role of type A/B behavioural patterns - Jin, Fang; Ashraf, Ahsan Ali; Ul Din, Sajid Mohy; Farooq, Umar; Zheng, Kengcheng; Shaukat, Ghazala (Frontiers in Psychology, 2022)
A multifaceted, holistic approach to identifying potential predictors is needed to eradicate workplace bullying. The current study investigated the impact of an unfavourable organisational climate that plays a role in breeding workplace bullying (social stressors). The present study also postulated that individual personality differences (Type A and Type B personality) mediate between a caring climate and workplace bullying. Similarly, the interaction between workplace bullying and personality impacts PTSD. We also checked the role of workplace bullying as a mediator between a caring climate and PTSD. This research tested all the proposed hypotheses (N = 298), and the study was conducted in Pakistan. The data is analysed using the two-step partial least square structural equation modelling (PLS-SEM) procedure. The first part assesses the measurement model, while in the second step, the structural model is evaluated. The results supported all the proposed hypotheses of this study. Type A behaviour moderated the caring climate—person-related bullying relationship, whereas it did not moderate the caring climate—work-related bullying in the suggested direction. Type A behaviour is moderated for both types of bullying and PTSD. Results also show significant indirect effects of a caring climate on PTSD through workplace bullying. This study will contribute theoretically to filling the literature gap on studies of climate-bullying and bullying-stress using contingency factors.